An alien parasite in a changing world – Ashworthius sidemi has lost its traditional seasonal dynamics - Magdálek, Jan; Škorpíková, Lucie; McFarland, Christopher; Vadlejch, Jaroslav (Frontiers in Veterinary Science, 2023)
A non-native nematode Ashworthius sidemi has emerged in captive fallow deer in Central and Eastern Europe over the last decade. Although this parasite has been spreading in the wild outside it’s native distributional range and colonising local European host species since the middle of the last century, limited information has been published on the seasonality of A. sidemi and its susceptibility to anthelmintics. To address this knowledge gap, we conducted a study to investigate seasonal dynamics of the non-native parasite in the current Central European climate conditions. We collected freshly voided faecal pellets at four-week intervals from February 2018 to February 2020 at a fallow deer reserve with a known history of A. sidemi presence. The faecal pellets obtained were pooled after each site visit (n=25) and coprocultured to obtain the third stage larvae of trichostrongylid nematodes at monthly intervals. Total genomic DNA was extracted from the recovered larvae. Using real-time multiplex PCR, A. sidemi DNA was detected in 17 out of 25 larval samples (68% prevalence). During the monitoring period, the annual administration of ivermectin based premix (Cermix) took place in January 2018, 2019 and 2020, and additionally a mixture of rafoxanide and mebendazole (Rafendazol) was administered once in spring 2019. The probability of parasite presence was significantly influenced by the time since the drug administration (p=0.048) and the mean temperature at the location (p=0.013). Larval samples negative for A. sidemi were always identified shortly after the drug administration. However, rapid pasture contamination by the parasite eggs from two to three months after Cermix administration and within one month after Rafendazol administration suggest only a short-lived efficacy of both administered drugs. The abundance of A. sidemi DNA was positively affected by mean temperature (p=0.044) and remained relatively stable throughout the monitoring period, with the highest peak in August 2018 and 2019. Pasture contamination with A. sidemi eggs occurred almost all year round, with the exception of the beginning of 2018, 2019 and 2020. These findings indicate adaptation of a non-native parasite to the current climatic conditions of the Czech Republic resulted in negligible seasonal patterns of parasite egg shedding.